Reviewing the controversy surrounding pre-treatment with P2Y12 inhibitors in acute coronary syndrome patients. (2nd July 2016) - Capodanno, Davide; Angiolillo, Dominick J.
ABSTRACT: Pretreatment with oral P2Y12 inhibitors occurs each time clopidogrel, prasugrel, ticagrelor are given to patients with suspected coronary artery disease before definition of the coronary anatomy. In acute coronary syndromes, the practice of administering oral P2Y12 inhibitors upstream has been the object of significant controversy in recent years, following the publication of two trials of pretreatment in non-ST-segment elevation acute coronary syndromes and ST-segment elevation myocardial infarction, respectively. The introduction in the market of cangrelor - the first intravenous P2Y12 inhibitor – represents a new opportunity but also a new challenge for clinicians. This article reviews current recommendations and supporting evidence surrounding pretreatment with oral and intravenous P2Y12 inhibitors in patients with acute coronary syndromes.